Intellectual property, human rights and development the role of NGOs and social movements - Matthews, Duncan; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar, 2011)
This insightful and important new book explores the role played by non-governmental-organizations (NGOs) in articulating concerns at the TRIPS Council, the WIPO, the WHO, the CBD-COP and the FAO that intellectual property rights can have negative consequences for developing countries. Duncan Matthews describes how coalitions of international NGOs have influenced the way that the relationship between intellectual property rights and development is understood, often framing the message as a human rights issue to emphasize these concerns and ensure that access to medicines, food security and the rights of indigenous peoples over their traditional knowledge are protected.
1. The interface between intellectual property, human rights and development -- 2. Public health and access to medicines -- 3. Agriculture, genetic resources and traditional knowledge -- 4. South Africa -- 5. Brazil -- 6. India -- 7. Emphasizing the link between intellectual property, human rights and development : the role of NGOs and social movements -- 8. Reappraising intellectual property rights and development : the role of NGOs and social movements.
Includes bibliographical references and index.
Keywords: Intellectual property; Human rights; Economic development; Non-governmental organizations; Social movements; Electronic books